Tolerance and its relationship to the five major factors of personality A sample of students from the Faculty of Education, Tishreen University (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The current research aimed to identify the relationship between tolerance and the five major factors of personality among students of the Faculty of Education at Tishreen University. To achieve the objectives of the research, the researcher used the Hartland scale of tolerance and the list of the five major factors of personality, prepared by Costa and Mary For melhem (2009). The tools were applied to a sample consisting of (185) male and female students from the last year students in the College of Education, of whom (95) were psychological counselors and (90) class teachers. The descriptive method was used. The results showed that tolerance came at an average level, as the arithmetic mean of the total degree of tolerance was (78.2), The results also indicated that there is a statistically significant direct correlation relationship at the level of significance 0.01 between tolerance and both ((extraversion, openness to experience, agreeableness, conscientiousness) among college students, While the inverse relationship was statistically significant at the level of 0.0 between neuroticism and tolerance among the sample members.